Ni-based organic coordination nano-particle, preparation method thereof, photoresist composition containing Ni-based organic coordination nano-particle and application of photoresist composition
By introducing Ni-based organic coordination nanoparticles into the photoresist and using their interaction with photoacid generators, the problems of large edge roughness and low resolution of the photoresist pattern are solved, and the lithographic performance of high resolution and low line roughness is achieved.
Patent Information
- Application Number
- CN202311147368.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-06
AI Technical Summary
The pattern edge roughness obtained by existing photoresist during lithography is large and the graphics resolution is low, which affects the application of lithography technology.
Ni-based organic coordination nanoparticles are used as components of the photoresist, and the polarity and solubility of the material are changed by interacting with the photoacid generator, thereby achieving the distinction between the photosensitive part and the light-shielding part during the development process and improving the photolithography performance.
The photolithography performance with high resolution, high sensitivity and low line roughness is achieved, and it has better results than traditional polymer and molecular glass photoresist.
Smart Images

Figure CN119569790A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photoresists, and in particular to Ni-based organic coordination nanoparticles and a preparation method thereof, a photoresist composition and an application thereof. Background Art
[0002] Photolithography is a technology that transfers the pattern on the mask to the substrate through photoresist under a certain amount of energy. It is the core of chip manufacturing. In the process of integrated circuit manufacturing, the cost of photolithography accounts for one-third or even more of the total cost; the size and quality of the photolithography greatly affect the performance of the chip. With the continuous development of photolithography technology, the line width of the light source continues to decrease, and the 13.5nm extreme ultraviolet light source exposure technology has gradually become the main choice for photolithography nodes below 7nm.
[0003] Photoresist refers to a corrosion-resistant thin film material whose solubility changes when exposed to ultraviolet light, electron beam, particle beam, extreme ultraviolet (EUV) or soft x-rays. It is widely used in pattern transfer in the manufacturing process of high-end micro-nano structures, including semiconductor integrated circuits, liquid crystal panel processing, and high-end optical device manufacturing. With the continuous advancement of semiconductor technology and the development of Moore's Law, semiconductor processes have continued to decrease, and higher requirements have been put forward for the reduction of processing feature sizes. In order to meet more advanced semiconductor processes and achieve smaller feature sizes, photolithography technology is also constantly developing, from i-line, G-line, deep ultraviolet (DUV), 193nm, immersion 193nm to extreme ultraviolet lithography, electron beam lithography and other fine processing methods. After the photoresist film is exposed and developed to form a photolithographic pattern, it will be dry or wet etched. The part of the substrate material not covered by the film is directly etched, while the substrate surface covered by the film is protected by the photoresist film and is not etched. Etching resistance is a very important evaluation index of photoresist. Excellent etching resistance can ensure that the photoresist can protect the substrate surface from damage during the etching process, effectively simplify the etching process, and greatly improve the yield of the finished etching product.
[0004] Traditional photoresists have complex components, including photoresist resin, photosensitive agents, leveling agents, stabilizers, dispersants, thickeners and solvents, etc. The production process is cumbersome and requires extremely high control technology for the ratio and purity. Since traditional photoresists are mostly macromolecular polymers and contain many functional additives, their complex composition leads to a wide size distribution of photoresists, with components of various sizes. Some size conformations can reach 10nm to 20nm, making the size of the photoresist pattern difficult to control and may cause many defects. In addition, for traditional photoresists, their scope of use is greatly affected by the wavelength of the light source, and different photoresists are required to match different light sources.
[0005] Extreme ultraviolet (EUV) lithography has attracted attention as a basic technology for manufacturing next-generation semiconductor devices. EUV lithography is a pattern forming technology that uses EUV rays having a wavelength of about 13.5 nanometers as an exposure light source. According to EUV lithography, it is known that extremely fine patterns (e.g., less than or equal to about 20 nanometers) can be formed in an exposure process during the manufacture of semiconductor devices.
[0006] However, in the prior art, the edge roughness of the pattern obtained by photolithography is large and the pattern resolution is low, which is not conducive to the application of photolithography technology. It is necessary to improve this. Summary of the invention
[0007] Based on this, it is necessary to propose a new Ni-based organic coordination nanoparticle and a preparation method thereof, a photoresist composition containing the same and its application to address the problem that the pattern edge roughness obtained by traditional photoresist lithography is large and the pattern resolution is low.
[0008] In one aspect, the present invention provides a Ni-based organic coordination nanoparticle, the general chemical formula of the nanoparticle is Ni m X n (CH3COO) t Y p H q , wherein X is m-toluate, CH3COO represents acetate, Y is a nitrogen-containing organic ligand, m, n, p, q are each independently selected from any integer from 1 to 20, and t is selected from any integer from 0 to 20; the nanoparticles are prepared by the following method: a nickel-containing compound, m-toluate and a nitrogen-containing organic ligand are mixed and stirred in an organic solvent and then post-treated, wherein the molar ratio of the nickel-containing compound:m-toluate and the nitrogen-containing organic ligand is (2-10):(4-10):(2-10).
[0009] Furthermore, the nitrogen-containing organic ligand is selected from any one or more of organic fatty amines and their derivatives, imidazole and their derivatives; nickel-containing compounds such as soluble nickel salts, such as nickel acetate, nickel acetate tetrahydrate, and nickel chloride.
[0010] Furthermore, the organic fatty amines are selected from any one or more of benzylamine and tripentylamine; the imidazole and its derivatives are selected from any one or more of N-methylimidazole and N-butylimidazole.
[0011] Furthermore, the nitrogen-containing organic ligand is selected from benzylamine, tripentylamine, N-methylimidazole, and N-butylimidazole.
[0012] Furthermore, the size of the Ni-based organic coordination nanoparticles is 2nm-5nm.
[0013] Furthermore, the post-treatment includes: stirring at 45°C-80°C for 5h-24h, then rotary evaporating at 35°C-50°C for 20min-80min using a rotary evaporator, and then vacuuming at 65°C-90°C in a vacuum oven for 2h.
[0014] Furthermore, the general structural formula of the nanoparticles is one of the following:
[0015] Ni 12 (C8H7COO)6(CH3COO) 18 (CH3C2N2H3)6(H2O)6;
[0016] Ni 12 (C8H7COO)6(CH3COO) 18 (C7H9N)6(H2O)6;
[0017] Ni 12 (C8H7COO)6(CH3COO) 18 (C7H 12 N2)6(H2O)6;
[0018] Ni 12 (C8H7COO)6(CH3COO) 18 (C 15 H 33 N)6(H2O)6.
[0019] The Ni-based organic coordination nanoparticles obtained by the present invention have a special structure. Under illumination conditions, they can interact with a photoacid generator (photoacid agent), change the polarity of the material, and agglomerate, causing the solubility of the Ni-based organic coordination nanoparticles to change before and after illumination. Due to these characteristics, the Ni-based organic coordination nanoparticles are used as photoresist components, and the solubility of the photosensitive part and the light-shielding part of the photoresist in the developer can be different. The photosensitive part agglomerates in the developer to reduce the solubility, while the light-shielding part does not agglomerate and dissolves in the developer, so that the non-exposed area can be removed after development to obtain a pattern of a desired shape. In particular, due to the special structure of the Ni-based organic coordination nanoparticles, compared to traditional polymer-type photoresists and molecular glass photoresists, the Ni-based organic coordination nanoparticles of the present invention are used as photoresist components to achieve more excellent lithography performances such as high resolution, high sensitivity, and low line roughness. The present invention finds that the introduction of benzoic acid ligands into Ni-based organic coordination nanoparticles can effectively reduce the crystallinity of the complex, improve the solubility of the material in organic reagents, and facilitate storage and application.
[0020] Furthermore, the above-mentioned photoresist composition further includes a photoacid and an organic dispersing solvent, wherein the photoacid preferably occupies 5wt%-10wt% of the composition, and the nanoparticles preferably occupy 3wt%-20wt% of the composition.
[0021] Further, the photoacid agent is selected from any one or more of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, 1,4-aminonaphthalenesulfonic acid, 2-amino-5,7-naphthalene disulfonic acid, tert-butylphenyl iodonium salt perfluorooctanesulfonic acid, triphenylsulfonium perfluorobutanesulfonic acid, triphenylsulfonium perfluorobutyl and triphenylsulfonium trifluorosulfonic acid.
[0022] Furthermore, the organic dispersing solvent is selected from any one or more of ethyl acetate, butyl acetate, propylene glycol monoethyl ether acetate, propylene glycol methyl ether acetate, 1-ethoxy-2-propanol, methanol, ethanol, and propanol. The solvent is preferably propylene glycol methyl ether acetate.
[0023] The present invention also provides a photolithography method, which uses the above-mentioned photoresist composition, drips the photoresist composition onto a substrate, rotates, heats, then exposes with an electron beam, mid-ultraviolet, deep ultraviolet or extreme ultraviolet, and develops with a developer.
[0024] The exposure dose of the exposure operation is 50 mJ / cm 2 ~500mJ / cm 2 The exposure dose should be controlled within an appropriate range. If the exposure dose is too small, the energy is too low, which is not conducive to the polymerization of the photoresist particles in the exposure area, and is not conducive to the formation of the difference in solubility between the exposure area and the non-exposure area, resulting in poor development effect. Compared with bare metal nanoparticles, nanoparticles containing organic ligands are more easily polymerized. If the exposure dose is too large, the organic ligands may fall off directly from the metal oxide to form fragments, and the photoresist particles can no longer undergo the exchange reaction of organic ligands, reducing the degree of polymerization in the exposure area.
[0025] Further, the developer is selected from any one or more mixtures of toluene, mesitylene, o-xylene, m-xylene, p-xylene, tetralin, decalin, cyclohexane, and n-propanol, and the developing temperature is room temperature or 20°C to 50°C.
[0026] The thickness of the pre-film layer after removing the organic dispersion solvent may be 10 nm to 100 nm. Specifically, the thickness of the pre-film layer may be 10 nm to 20 nm, 20 nm to 30 nm, 30 nm to 40 nm, 40 nm to 50 nm, 50 nm to 60 nm, 60 nm to 70 nm, 70 nm to 80 nm, 80 nm to 90 nm, 90 nm to 100 nm.
[0027] Furthermore, the above-mentioned nanoparticles are used in the field of photoresists, especially electron beam, mid-ultraviolet, deep ultraviolet and / or extreme ultraviolet photoresists.
[0028] The exposure condition is selected from any one of mid-ultraviolet, deep ultraviolet, electron beam, and extreme ultraviolet. The photoresist composition of the present invention can be used in any exposure condition.
[0029] The substrate is selected from a silicon plate. Other substrates that are insoluble in the developer can also be selected according to actual needs.
[0030] Regarding masks, deep ultraviolet and longer wavelength light sources are transmissive masks, extreme ultraviolet is a reflective mask, and the electron beam exposes according to the pattern set by the software. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The cluster structure of the Ni-based organic coordination nanoparticle single crystal analyzed in Example 1 of the present invention;
[0032] Figure 2 This is a dynamic light scattering diagram of the Ni-based organic coordination nanoparticles of Example 1 of the present invention;
[0033] Figure 3 is the infrared spectrum of the Ni-based organic coordination nanoparticles of Example 1 of the present invention;
[0034] Figure 4 This is the XPS spectrum of the Ni-based organic coordination nanoparticles of Example 1 of the present invention;
[0035] Figure 5 The cluster structure of the Ni-based organic coordination nanoparticle single crystal analyzed in Example 3 of the present invention;
[0036] Figure 6 The dynamic light scattering diagram of the Ni-based organic coordination nanoparticles of Example 3 of the present invention is
[0037] Figure 7 The powder XRD spectra of the Ni-based organic coordination nanoparticles of Examples 1, 2, and 4 of the present invention;
[0038] Figure 8 This is a dynamic light scattering diagram of the Ni-based organic coordination nanoparticles of Example 2 of the present invention;
[0039] Fig. 9 This is a dynamic light scattering diagram of the Ni-based organic coordination nanoparticles of Example 4 of the present invention;
[0040] Figure 10-Figure 19 This is a photolithography imaging microscope photograph of the Ni-based organic coordination nanoparticles of Example 1 of the present invention;
[0041] Fig. 20 and Fig.21 This is a photolithography imaging microscope photograph of the Ni-based organic coordination nanoparticles of Example 2 of the present invention;
[0042] Fig. 22 This is a photolithography imaging microscope photograph of the Ni-based organic coordination nanoparticles of Example 3 of the present invention;
[0043] Fig.23 This is a photolithography imaging microscope photograph of the Ni-based organic coordination nanoparticles of Example 4 of the present invention. DETAILED DESCRIPTION
[0044] Example 1
[0045] 5.44g (40mmol) m-toluic acid (m-toluic acid) and 4.98g (20mmol) Nickel acetatetetrahydrate (nickel acetate tetrahydrate) were added to a 150ml flask, dissolved with 45mL THF, heated and stirred at 65℃ for 5 minutes, and then 1.67g methylimidazole (1-methylimidazole) was added, and heated and stirred at 65℃ overnight. After obtaining a green solution, the solution was allowed to stand at low temperature for 15 days to obtain crystals. The structure of the nanoparticles can be obtained through single crystal analysis test, and the analysis showed that Figure 1 The molecular structure shown is Ni 12 (C8H7COO)6(CH3COO) 18 (CH3C2N2H3)6(H2O)6, named Ni-mTA-MI, is a multinuclear complex with m-toluic acid, N-methylimidazole, acetate and water as ligands and containing 12 Ni rings.
[0046] Further, the green solution was rotary evaporated in a rotary evaporator at 100 mbar for 2 h to obtain a green viscous fluid, which was placed in a vacuum oven at 80°C for 4 h to obtain a photoresist product. The photoresist product was dissolved in a 5% PGMEA solution, and the solution was subjected to a DLS particle size test. The results are as follows: Figure 2 As shown. The infrared spectrum test and XPS test were performed on it, and the results were as follows Figure 3-Figure 4 The test results shown in FIG. 4 show that the substance prepared by the method of this embodiment is metal organic ligand nanoparticles.
[0047] Example 2
[0048] 5.44g (40mmol) m-toluic acid (m-toluic acid) and 4.98g (20mmol) Nickel acetatetetrahydrate (nickel acetate tetrahydrate) were added to a 150ml flask, dissolved with 45mL THF, heated and stirred at 65℃ for 5 minutes, and then 2.16g Benzylamine was added, and heated and stirred at 65℃ overnight. After obtaining a green solution, the solution was allowed to stand at low temperature for 15 days to obtain crystals. The powder XRD analysis test showed that the result was Figure 7 The XRD results of this embodiment are basically consistent with those of embodiment 1. It is speculated that in this embodiment, Benzylamine replaces methylimidazole in embodiment 1, and the molecular structure is Ni 12 (C8H7COO)6(CH3COO) 18 (C7H9N)6(H2O)6, named Ni-mTA-BA.
[0049] Further, the green solution was rotary evaporated in a rotary evaporator at 100 mbar for 2 h to obtain a green viscous fluid, which was placed in a vacuum oven at 80°C for 4 h to obtain a photoresist product. The photoresist product was dissolved in a 5% PGMEA solution, and the solution was subjected to a DLS particle size test. The results are as follows: Figure 8 It can be seen that the substance prepared by the method of this embodiment is metal organic ligand nanoparticles.
[0050] Example 3
[0051] 5.44g (40mmol) m-toluic acid (m-toluic acid) + 4.98g (20mmol) Nickel acetatetetrahydrate (nickel acetate tetrahydrate) were added to a 150ml flask, dissolved with 45mL THF, heated and stirred at 65℃ for 5 minutes, and then 2.51g 1-Butylimidazole (N-butylimidazole) was added, and heated and stirred at 65 overnight. After obtaining a green solution, the solution was allowed to stand at low temperature for 15 days to obtain crystals. The structure of the nanoparticles can be obtained through single crystal analysis test, and the analysis showed that Figure 5 The molecular structure shown is Ni 12 (C8H7COO)6(CH3COO) 18 (C7H 12 N2)6(H2O)6, named Ni-mTA-BI, is a multinuclear complex with m-toluic acid, N-butylimidazole, acetate and water as ligands and containing 12 Ni rings.
[0052] Further, the green solution was rotary evaporated in a rotary evaporator at 100 mbar for 2 h to obtain a green viscous fluid, which was placed in a vacuum oven at 80°C for 4 h to obtain a photoresist product. The photoresist product was dissolved in a 5% PGMEA solution, and the solution was subjected to a DLS particle size test. The results are as follows: Figure 6 It can be seen that the substance prepared by the method of this embodiment is metal organic ligand nanoparticles.
[0053] Example 4
[0054] 5.44g (40mmol) m-toluic acid + 4.98g (20mmol) Nickel acetatetetrahydrate were added to a 150ml flask, dissolved with 45mL THF, heated and stirred at 65℃ for 5 minutes, and then 4.59g Triamylamine was added, heated and stirred at 65℃ overnight. After obtaining a green solution, the solution was left to stand at low temperature for 15 days to obtain crystals. The analytical test results are as follows: Figure 7 , the molecular structure is speculated to be Ni 12 (C8H7COO)6(CH3COO) 18 (C 15 H 33 N)6(H2O)6, named Ni-mTA-TAA.
[0055] Further, the green solution was rotary evaporated in a rotary evaporator at 100 mbar for 2 h to obtain a green viscous fluid, which was placed in a vacuum oven at 80°C for 4 h to obtain a photoresist product. The photoresist product was dissolved in a 5% PGMEA solution, and the solution was subjected to a DLS particle size test. The results are as follows: Fig. 9 It can be seen that the substance prepared by the method of this embodiment is metal organic ligand nanoparticles.
[0056] Embodiment 5-8
[0057] 0.5 wt % PAG-1 (N-hydroxynaphthaleneimide trifluoromethanesulfonate) was added to the prepared solution of Ni-mTA-MI in Example 1 (5.0 wt %), the solvent was propylene glycol monoethyl ether acetate (PGMEA), and stirred for 5 minutes until it was completely dissolved to obtain a photoresist mixed solution.
[0058] Filter the photoresist mixture twice with a filter head, then place the silicon wafer on a coating machine, drip the photoresist onto the silicon wafer, set the speed to 2000r / min, and rotate for 1min. Then heat on a hot plate at 90℃ for 1min. UV exposure-development in progress: The specific conditions are to expose the film to 254nm UV radiation with an exposure dose of 150mJ / cm 2The contact exposure mask was used. The developer was meta-xylene, and the exposure time was 5s, 10s, and 15s respectively to obtain a line exposure pattern with a half-pitch of 1-10μm. Figure 10-12 Electron beam exposure-development was performed with an exposure dose of 400 μC / cm 2 , beam intensity 1.0~3.0A, o-xylene as developer, development time 15s, half-pitch 100nm line, the test pattern is shown in Fig.13 .
[0059] Examples 9-11
[0060] 0.5 wt % PAG-1 (N-hydroxynaphthaleneimide trifluoromethanesulfonate) was added to the prepared solution of Ni-mTA-MI in Example 1 (5.0 wt %), the solvent was propylene glycol monoethyl ether acetate (PGMEA), and stirred for 5 minutes until it was completely dissolved to obtain a photoresist mixed solution.
[0061] Filter the photoresist mixture twice with a filter head, then place the silicon wafer on a coating machine, add the photoresist to the silicon wafer, set the speed to 2000r / min, and rotate for 1min. Then heat it on a hot plate at 100℃ for 1min. UV exposure-development in progress: The specific conditions are to expose the film to 254nm UV radiation with an exposure dose of 150mJ / cm 2 The contact exposure mask was used. The developer was meta-xylene, and the exposure time was 5s, 10s, and 15s respectively to obtain a line exposure pattern with a half-pitch of 1-10μm. Figure 14-16 .
[0062] Examples 12-14
[0063] 0.5 wt % PAG-1 (N-hydroxynaphthaleneimide trifluoromethanesulfonate) was added to the prepared solution of Ni-mTA-MI in Example 1 (5.0 wt %), the solvent was propylene glycol monoethyl ether acetate (PGMEA), and stirred for 5 minutes until it was completely dissolved to obtain a photoresist mixed solution.
[0064] Filter the photoresist mixture twice with a filter head, then place the silicon wafer on a coating machine, add the photoresist to the silicon wafer, set the speed to 2000r / min, and rotate for 1min. Then heat it on a hot plate at 110℃ for 1min. UV exposure-development in progress: The specific conditions are to expose the film to 254nm UV radiation with an exposure dose of 150mJ / cm 2 The contact exposure mask was used. The developer was meta-xylene, and the exposure time was 5s, 10s, and 15s respectively to obtain a line exposure pattern with a half-pitch of 1-10μm. Figure 17-Figure 19 .
[0065] Examples 13-16
[0066] 0.5 wt % PAG-1 (N-hydroxynaphthaleneimide trifluoromethanesulfonate) was added to the prepared solution of Ni-mTA-BA in Example 2 (5.0 wt %), the solvent was propylene glycol monoethyl ether acetate (PGMEA), and stirred for 5 minutes until it was completely dissolved to obtain a photoresist mixed solution.
[0067] Filter the photoresist mixture twice with a filter head, then place the silicon wafer on a coating machine, drip the photoresist onto the silicon wafer, set the speed to 2000r / min, and rotate for 1min. Then heat on a hot plate at 90℃, 100℃, and 110℃ for 1min. UV exposure-development in progress: The specific conditions are to expose the film to 254nm UV radiation with an exposure dose of 150mJ / cm 2 , using contact exposure mask. The developer is meta-xylene, and the development is 10s to obtain a line exposure pattern with a half-pitch of 1-10μm. Fig. 20 , Fig. 20 Figures A, B, and C correspond to 90°C, 100°C, and 110°C, respectively. Electron beam exposure-development was performed with an exposure dose of 400 μC / cm 2 , beam intensity 1.0 ~ 3.0A, using mesitylene as developer, developing time 15s, get half-pitch 100nm line, the test pattern is shown in Fig.21 .
[0068] Examples 17-19
[0069] 0.5 wt % PAG-1 (N-hydroxynaphthaleneimide trifluoromethanesulfonate) was added to the prepared solution of Ni-mTA-BI in Example 3 (5.0 wt %), the solvent was propylene glycol monoethyl ether acetate (PGMEA), and stirred for 5 minutes until it was completely dissolved to obtain a photoresist mixed solution.
[0070] Filter the photoresist mixture twice with a filter head, then place the silicon wafer on a coating machine, add the photoresist to the silicon wafer, set the speed to 2000r / min, and rotate for 1min. Then heat on a hot plate at 90℃, 100℃, and 110℃ for 1min. In progress UV exposure-development: The specific conditions are to expose the film to 254nm UV radiation with an exposure dose of 1000mJ / cm 2 , using contact exposure mask. The developer is meta-xylene, and the development is 10s to obtain a line exposure pattern with a half-pitch of 1-10μm. Fig. 22 ,in, Fig. 22Figures A, B, and C correspond to 90°C, 100°C, and 110°C, respectively.
[0071] Examples 20-22
[0072] 0.5 wt % PAG-1 (N-hydroxynaphthaleneimide trifluoromethanesulfonate) was added to the prepared solution of Ni-mTA-TAA in Example 4 (5.0 wt %), the solvent was propylene glycol monoethyl ether acetate (PGMEA), and stirred for 5 minutes until it was completely dissolved to obtain a photoresist mixed solution.
[0073] Filter the photoresist mixture twice with a filter head, then place the silicon wafer on a coating machine, drip the photoresist onto the silicon wafer, set the speed to 2000r / min, and rotate for 1min. Then heat on a hot plate at 90℃, 100℃, and 110℃ for 1min. UV exposure-development in progress: The specific conditions are to expose the film to 254nm UV radiation with an exposure dose of 2000mJ / cm 2 , using contact exposure mask. The developer is meta-xylene, and the development is 10s to obtain a line exposure pattern with a half-pitch of 1-10μm. Fig.23 ,in, Fig.23 Figures A, B, and C correspond to 90°C, 100°C, and 110°C, respectively.
[0074] In summary, the present invention obtains a variety of effective nanoparticles and corresponding compositions, verifies the structure and has good lithography performance under mid-ultraviolet and EBL conditions, and can achieve better lithography performance such as high resolution, high sensitivity, and low line roughness.
Claims
1. A Ni-based organic coordination nanoparticle, characterized in that: The general chemical formula of the nanoparticles is Ni m X n (CH3COO) t Y p H q , wherein X is m-toluate, CH3COO represents acetate, Y is a nitrogen-containing organic ligand, m, n, p, q are each independently selected from any integer from 1 to 20, and t is selected from any integer from 0 to 20; the nanoparticles are prepared by the following method: a nickel-containing compound, m-toluate and a nitrogen-containing organic ligand are mixed and stirred in an organic solvent and then post-treated, wherein the molar ratio of the nickel-containing compound:m-toluate and the nitrogen-containing organic ligand is (2-10):(4-10):(2-10).
2. The Ni-based organic coordination nanoparticles according to claim 1, characterized in that: The nitrogen-containing organic ligand is selected from any one or more of organic fatty amines and their derivatives, imidazole and their derivatives; the nickel-containing compound is selected from nickel acetate and nickel acetate tetrahydrate.
3. The Ni-based organic coordination nanoparticles according to claim 2, characterized in that: The organic fatty amines are selected from any one or more of benzylamine and tripentylamine; the imidazole and its derivatives are selected from any one or more of N-methylimidazole and N-butylimidazole.
4. The Ni-based organic coordination nanoparticles according to claim 3, characterized in that: The nitrogen-containing organic ligand is selected from benzylamine, tripentylamine, N-methylimidazole, and N-butylimidazole.
5. The Ni-based organic coordination nanoparticles according to any one of claims 1 to 4, characterized in that: The size of the Ni-based organic coordination nanoparticles is 2nm-5nm.
6. The Ni-based organic coordination nanoparticles according to any one of claims 1 to 4, characterized in that: The post-treatment comprises: stirring at 45° C.-80° C. for 5 h-24 h, then using a rotary evaporator at 35° C.-50° C. for 20 min-80 min, and then vacuuming at 65° C.-90° C. in a vacuum oven for 2 h.
7. The Ni-based organic coordination nanoparticles according to any one of claims 1 to 4, characterized in that: The general structural formula of the nanoparticles is one of the following: Ni 12 (C8H7COO)6(CH3COO) 18 (CH3C2N2H3)6(H2O)6; Ni 12 (C8H7COO)6(CH3COO) 18 (C7H9N)6(H2O)6; Ni 12 (C8H7COO)6(CH3COO) 18 (C7H 12 N2)6(H2O)6; It’s 12 (C8H7COO)6(CH3COO) 18 (C 15 H 33 N)6(H2O)6。 8. A photoresist composition, characterized in that The invention comprises the Ni-based organic coordination nanoparticles as described in any one of claims 1 to 7.
9. The photoresist composition according to claim 8, characterized in that The composition also includes a photoacid agent and an organic dispersing solvent, wherein the photoacid agent occupies 5wt%-10wt% of the composition, and the nanoparticles occupies 3wt%-20wt% of the composition.
10. The photoresist composition according to claim 9, characterized in that The photoacid agent is selected from any one or more of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, 1,4-aminonaphthalenesulfonic acid, 2-amino-5,7-naphthalene disulfonic acid, tert-butylphenyl iodonium salt perfluorooctanesulfonic acid, triphenylsulfonium perfluorobutanesulfonic acid, triphenylsulfonium perfluorobutyl and triphenylsulfonium trifluorosulfonic acid.
11. The photoresist composition according to claim 9, characterized in that The organic dispersing solvent is selected from any one or more of ethyl acetate, butyl acetate, propylene glycol monoethyl ether acetate, propylene glycol methyl ether acetate, 1-ethoxy-2-propanol, methanol, ethanol, and propanol.
12. A photolithography method, characterized in that: The photoresist composition according to any one of claims 8 to 11 is added dropwise to a substrate, rotated, heated, exposed to electron beam, mid-ultraviolet, deep ultraviolet or extreme ultraviolet light, and developed with a developer.
13. The photolithography method according to claim 12, characterized in that: The exposure dose is 50mJ / cm 2 ~500mJ / cm 2 .
14. The photolithography method according to claim 13, characterized in that: The developer is selected from any one or more mixtures of toluene, mesitylene, o-xylene, m-xylene, p-xylene, tetralin, decalin, cyclohexane, and n-propanol, and the developing temperature is 20° C. to 50° C.
15. The use of the Ni-based organic coordination nanoparticles according to any one of claims 1 to 7, characterized in that: Used in the field of photoresists, especially electron beam, mid-UV, deep UV and / or extreme UV photoresists.
Citation Information
Patent Citations
Photoresist, patterning method of photoresist and method for generating printed circuit board
CN112462572A
Zinc-based metal organic nanoparticles, preparation method thereof and photoresist
CN114675488A
Radiation-sensitive composition and pattern-forming method
US20190258161A1
Radiation-sensitive composition, pattern-forming method and compound
US20200387068A1